Efficacy of Cognition Support Formula® on cognitive function in older adults with subjective cognitive impairment: a protocol for a 26-week, randomised, double-blind, placebo-controlled trial - Adele E. Cave; Dennis H. Chang; Gerald W. Münch; Genevieve Z. Steiner (Trials, 2019)
Abstract Background Due to an ageing population in Australia there has been an increase in the number of older adults with subjective cognitive impairment (SCI), a self-reported decline in cognitive function associated with an increased risk of mild cognitive impairment and dementia. There is no current, recommended treatment for SCI; therefore, the effectiveness of a supplement approved by the Therapeutic Goods Association that has the potential to enhance cognitive function in an at-risk cohort should be tested. The primary aim of this proposed research is to determine the efficacy of 6 months of treatment with BioCeuticals Cognition Support Formula® (containing Bacopa monniera (brahmi), Ginkgo biloba, Panax ginseng and alpha-lipoic acid) on cognition in older adults with SCI (utilising the CogState® one card learning and identification tests as co-primary outcome measures of visual short-term memory and attention; mean speed (ms), accuracy (%), and total number of hits, misses, and anticipations) compared with placebo. The secondary aims are to assess an improvement in other cognitive domains (executive functioning, processing speed, and working memory), evaluate safety, adverse effects, and determine efficacy on mood, fatigue, and neurocognition. It is expected that improvements across the study timepoints in the co-primary outcomes in the active treatment group (compared with placebo) will be evident. Method One-hundred and twenty participants will be recruited for the randomised, double-blind, placebo-controlled study. Participants will be randomly assigned to one of the treatment groups (active or placebo) at a 1:1 ratio, and will be required to complete a series of cognitive (using CogState®), mood (using the Depression, Anxiety, Stress Scale (DASS-42) and Short Health Anxiety Inventory (SHAI)), and fatigue (using the Functional Assessment of Chronic Illness Therapy Fatigue Scale (FACIT-F)) tasks at baseline (0 months), the midpoint (3 months), and the endpoint (6 months). These tasks will be evaluated between timepoints (baseline vs. midpoint, midpoint vs. endpoint, and baseline vs. endpoint). Neurocognition will be measured by electroencephalography at baseline and at the endpoint in half of the participants. Adverse effects will be documented over the 6-month trial period. Discussion This is the first study to test the efficacy of Cognition Support Formula® on cognition in older adults with SCI. As people with SCI have an increased risk of dementia, and there are limited treatments options for this population, it is important to assess a supplement that has the potential to enhance cognitive function. Trial registration Universal Trial Number (UTN), U1111–1196-9548. Australian New Zealand Clinical Trials Registry, ACTRN12617000945325. Registered on 30 June 2017.